LED as laboratory test source for astronomical intensity interferometry - Zmija, Andreas; Deiml, Peter; Malyshev, Dmitry; Zink, Adrian; Anton, Gisela; Michel, Thilo; Funk, Stefan (Optics Express, 2020)
The challenge of astronomical intensity interferometry is to detect the small photon-bunching signals of distant sources with a broad optical bandwidth. We have built a Hanbury Brown-Twiss-like laboratory intensity interferometer with a focus on a relatively broad bandwidth (1 nm FWHM optical filter) and high photon rates (up to 10 MHz) per channel compared to typical (non-astronomical) intensity interferometry applications. As a light source we use a green LED to simulate starlight. The LED has proven to be a compact high-power source of stochastic light with a special advantage of a small emission area, which favours spatial coherence. Using single-photon correlations, we detect a bunching signal in the second-order correlation function with a coherence time of <1 ps and an amplitude of <4 · 10−4 and describe signal and background quantitatively for a 40 hours measurement. In this paper we show our setup, present the correlation measurements and compare them to theoretical expectations.
CRIS-Team Scopus Importer:2020-02-21